Rhizophora mangle L. (red mangrove): A species with potential therapeutic uses - Ada I. Regalado; Luz M. Sánchez; Betty Mancebo (Journal of Pharmacy & Pharmacognosy Research, 2016)
Check the properties attributed to medicinal plants is of vital importance as an alternative in the medical therapy and as a source of development of new drugs. Medicinal plants offer a path with great possibilities, an encouraging alternative for the control of various diseases in man. Mangroves are a resource of great significance for Cuba and the world, mangrove vegetation is represented in this country for four tree species, where Rhizophora mangle L. also known as red mangrove, is now the dominant species. Due to the pharmacological results found in this species as healing, antiseptic, antimicrobial, anti-ulcer, treatment of open wounds, anti-inflammatory, antioxidant, antidiarrheal, insecticide, larvicide among others; it could be an important source of new products aimed at solving health problems of great current relevance, but using this species for drug development has been limited by the damage it can cause to the ecosystem over-exploitation of mangroves. The objective of this scientific review is to show the benefits and therapeutic potential of R. mangle from a review of existing information and the main results in the researches on this species.